Flaskô na contramão: a experiência de controle operário em uma fábrica ocupada no Brasil - Tadokoro, Ricardo Takayuki (2013)
Lately we can observe the closure and abandon of companies in a new international arrangement pressed by the monopolist competition of the large capital inserted starting on the process of worldwide financialization and of a structural crisis marching. In response to these events, workers about to be unemployed resisted and assumed the control of companies in a perspective of community and self-management which became known as Occupied Factories . The objective is to analyze the extent of the experience of occupied factories by workers are historical alternatives to the capitalist mode of production or merely part of a survival strategy against a front frame of a structural crisis of the capital. We use the bibliographic research and the field incursions where are analyzed the conditions and forms of organization, mobilization and resistance of the Flaskô workers. The contemporary factories occupations and the system of worker s control are part of a historical and dialectical process of the capitalist society formation. Thereby we will put in evidence an experience which largely refers to the process of the class struggle that reverberates deep contradictions and social antagonisms still unresolved.